2023
DOI: 10.1177/00048674231175618
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of individual mental health and psychological resilience after Australia’s 2019–2020 bushfires

Abstract: Aims: We assessed the mental health effects of Australia’s 2019–2020 bushfires 12–18 months later, predicting psychological distress and positive psychological outcomes from bushfire exposure and a range of demographic variables, and seeking insights to enhance disaster preparedness and resilience planning for different profiles of people. Methods: We surveyed 3083 bushfire-affected and non-affected Australian residents about their experiences of bushfire, COVID-19, psychological distress (depression, anxiety,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…A meta-analysis found that PTSD and depression are markedly higher in cohorts affected by environmental disasters including earthquakes, tsunami, hurricanes, volcanic eruptions, and fires [4]. Direct experience of wildfires is associated with an increased risk of depression, anxiety, PTSD, and substance abuse, and has additional indirect effects on mental health due to loss of income, loss of home, displacement, and loss of possessions [9][10][11]. Effects are most severe among those who feared for their lives or lost someone close to them to the fires [12].…”
Section: Wildfires and Mental Healthmentioning
confidence: 99%
“…A meta-analysis found that PTSD and depression are markedly higher in cohorts affected by environmental disasters including earthquakes, tsunami, hurricanes, volcanic eruptions, and fires [4]. Direct experience of wildfires is associated with an increased risk of depression, anxiety, PTSD, and substance abuse, and has additional indirect effects on mental health due to loss of income, loss of home, displacement, and loss of possessions [9][10][11]. Effects are most severe among those who feared for their lives or lost someone close to them to the fires [12].…”
Section: Wildfires and Mental Healthmentioning
confidence: 99%
“…10 Notwithstanding the unique features of major bushfires and a public health emergency, few studies have yet considered specific impacts on mental health and well-being of the Black Summer bushfires and COVID-19 pandemic. Available studies have mainly comprised cross-sectional surveys of adolescents 11 and adults, 12 teachers 13 and older adults, 14 with one study using a mood-monitoring application that tracked changes over time. 15 The latter suggested that symptoms of depression increased during the bushfires and remained elevated subsequently during pandemic restrictions, whereas experiences of anxiety and reduced social connectedness were observed during the pandemic (relative to when bushfires were active).…”
mentioning
confidence: 99%
“… 15 The latter suggested that symptoms of depression increased during the bushfires and remained elevated subsequently during pandemic restrictions, whereas experiences of anxiety and reduced social connectedness were observed during the pandemic (relative to when bushfires were active). 15 Cross-sectional surveys also indicate that bushfire and pandemic impacts are both associated with reduced mental health 11 and well-being 13 (although links with pandemic stressors may be attenuated when controlling for factors such as financial difficulties), 12 as well as greater social isolation. 14 By contrast, relevant studies have found no evidence of interactions between pandemic and bushfire impacts, although complex relationships have been observed with adverse childhood experiences (suggesting compounding effects of disasters and earlier trauma histories).…”
mentioning
confidence: 99%